Asupan Lemak, Rasio Lingkaran Pinggang-Tinggi Badan Dan Aktivitas Fisik Dengan Tekanan Darah Pada - Kuna, Sri Fadlia; Solikhah, Lilik Sofiatus; Nurdiana, Nurdiana (Poltekkes Kemenkes Jambi, 2024)
Background: Hypertension continues to increase in Indonesia. High blood pressure is influenced by several factors, including intake of foods high in fat, obesity, and decreased physical activity. The aim of this study was to determine the relationship between fat intake, waist to height ratio (RLPTB), and blood pressure in Widia Nusantara University students. Method: Cross-sectional design for current students of the 2021-2022 class of Widiya Nusantara University. The sample consisted of 254 students selected using purposive sampling technique. Results: This study showed that 72.8% of students had high fat intake, 35.4% had low physical activity, 56.7% had central obesity, 28.3% had prehypertension, and 8.3% had hypertension. There was no significant relationship fat consumption interval, trunk proportions, The relationship between exercise and blood pressure in students (p = 0.215). 0.466; and 0.488. Conclusion: There is no relationship between fat intake, RLPTB, physical activity and blood pressure in Widia Nusantara University students.